2007
DOI: 10.1038/sj.jhh.1002293
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy and safety of irbesartan/HCTZ combination therapy with irbesartan and HCTZ monotherapy in the treatment of moderate hypertension

Abstract: This prospective, double-blind, parallel-group study randomized patients with moderate hypertension (seated systolic blood pressure (SeSBP) 160-179 mm Hg when seated diastolic blood pressure (SeDBP) o110 mm Hg; or SeDBP 100-109 mm Hg when SeSBP o180 mm Hg) 3:1:1 to treatment with irbesartan 300 mg/hydrochlorothiazide (HCTZ) 25 mg combination therapy (n ¼ 328), irbesartan 300 mg monotherapy (n ¼ 106) or HCTZ monotherapy 25 mg (n ¼ 104). Treatment was initiated at half dose, with forced titration to full dose af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Th e INCLUSIVE TRIAL (66) had 3% serious adverse events with 3 occurring in the placebo arm, 4 in the HCTZ monotherapy 12.5 mg/day, 8 in the irbesartan/HCTZ 150/12.5 mg/day, and 7 in the irbesartan/HCTZ 200/25 mg/day. All were judged as unrelated to the medication except for one event of hypotension in the irbesartan/HCTZ 150/12.5 mg/day which was probably drug related (66).…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e INCLUSIVE TRIAL (66) had 3% serious adverse events with 3 occurring in the placebo arm, 4 in the HCTZ monotherapy 12.5 mg/day, 8 in the irbesartan/HCTZ 150/12.5 mg/day, and 7 in the irbesartan/HCTZ 200/25 mg/day. All were judged as unrelated to the medication except for one event of hypotension in the irbesartan/HCTZ 150/12.5 mg/day which was probably drug related (66).…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%
“…All were judged as unrelated to the medication except for one event of hypotension in the irbesartan/HCTZ 150/12.5 mg/day which was probably drug related (66). Lapuerta et al (115) actually reported more adverse events with irbesartan monotherapy than irbesartan/HCTZ combination therapy 300/25 mg/day (36.1% versus 29.9%).…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 99%
“…The RAPiHD moderate study enrolled patients with moderate hypertension, defined as SBP of 160 to 179 mmHg and DBP of <110 mmHg in untreated patients; or SBP ≥ 150 to <180 mmHg and DBP ≥ 95 to <110 mmHg in patients uncontrolled on monotherapy 48. Following a 3-week placebo washout period, patients were randomized 3:1:1 to irbesartan/HCTZ 300/25 mg (n = 328), irbesartan 300 mg monotherapy (n = 106) or HCTZ monotherapy 25 mg (n = 104).…”
Section: Efficacy Of Fd Irbesartan/hctz Combinationmentioning
confidence: 99%
“…In a pooled analysis 18 of the two RAPiHD studies (moderate and severe), 10,24 37.0% adverse events occurred, which were ascribed to the medication in 12.5% of the patients (0.9% serious). These figures were only slightly raised compared with irbesartan monotherapy.…”
Section: Compliance and Tolerabilitymentioning
confidence: 99%